Development of analytical methodologies for the quality control of liquors using nearby infrared spectroscopy and multivariate analysis - Tapiero Cuellar, José Libardo; Valle Mora, Alexis (Revista Colombiana de Investigaciones Agroindustriales, 2022)
The application of NIR near-infrared spectroscopy and multivariate analysis as a rapid analysis technique in the quantification of the content of methanol in commercially distributed liqueurs (Aguardiente), to identify if these liqueurs exceed the methanol limits established in the standard. AOAC 972.11 (100 mg / dm3) (AOAC 972.11, 1973). For this, in a first stage, the application of a design of ternary mixtures methanol-ethanol-water (MDOE) was carried out in order to reduce correlation effects between the variables, in addition to achieving multivariate models that include variability important by expanding the calibration range that act under process conditions and in commercialization sites. The second stage was associated with the recording of the NIR spectra of the prepared samples, to obtain a data matrix, from which the multivariate models are developed using different algorithms. The results obtained showed that it is possible to develop a rapid analysis method for the quantification of methanol in Aguardiente samples, using NIR spectroscopy and the multivariate models constructed, in which a Mean Square Prediction Error (RMSEP) of 0.7766 was obtained. % and correlation coefficient (R2) of 0.9553.